Reduction of Colour from Indigo Dye-Rich Wastewater by Electro-Coagulation using Iron (Fe) and Aluminum (Al) Electrodes - Badejo, A. A.; Nkeshita, F. C.; Adelasoye, O. J.; Adeyanju, O. P. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Indigo dyes are important substances in the Adire Textile industry which are not environmentally friendly because they produce colored effluent. This study evaluated the performance of a batch-scale electro-coagulation (EC) technique for Indigo dye-rich wastewater treatment. A pilot-scale EC unit using Iron (Fe) and Aluminum (Al) electrodes, having a mono-polar parallel arrangement with a constant inter-electrode distance of 10 mm was developed. The Fe anode and Al cathode had effective areas of 16.50 and 22.75 cm2 respectively. The impact of pH, Sodium Chloride (NaCl), and electrolysis time on EC performance was assessed by calculating the color reduction. A three-factor three-level Box Benkhen Design with three center points was used to generate fifteen experimental runs using NaCl, pH, and electrolysis time as independent variables and color removal efficiency as the response variable. A regression analysis was performed after the results of the experimental data were fitted to a full quadratic model resulting in the generation of regression coefficients. The model was inversely transformed and modified to make it significant. The results show that the optimum pH and NaCl concentration were 3 and 4 g/l respectively with electrolysis time of 35 minutes. Under these optimum conditions, the percentage of colour removal was 32.78% with a predicted value of 80%. An R2 value of 83.45% was obtained and ANOVA verified that the accuracy of the proposed polynomial model is acceptable. Therefore, it is noteworthy that an EC technique could be used in reducing color from Indigo Dye-rich wastewater in textile industry.